Smart Classrooms, Smarter Teachers: A Deep Dive into AI-Driven Educational Enhancement - Deepti Chopra, Praveen Arora (Journal of Informatics Education and Research, 2023)
In the digital era, the introduction of Artificial Intelligence (AI) in education has emerged as a pivotal force in shaping the future of teaching and learning. This book chapter explores the transformative impact of AI on education, with the main focus on empowering educators with innovative tools. This chapter discusses about role of AI in shaping the education system, emphasizing its potential in revolutionizing the traditional approaches, providing a personalized user learning experiences, and offering detailed insights into students performance. It discusses about AI tools used to assist teachers in creation of personalized learning platforms, content creation and delivery, virtual teaching assistants and predictive analytics for early intervention in students performance. This chapter discusses about real-world examples of how AI tools have enhanced educational quality and have enabled teachers in experiencing enriching teaching experiences. It also discusses about issues of bias and data privacy and the importance of responsible AI implementation in educational system. This chapter takes into account emerging trends, potential challenges, and the continuous evolution of AI in education. By considering intersection of technology and pedagogy, this chapter aims to deliver a comprehensive understanding of how AI tools are reshaping the educational landscape and contributing to a new era of quality education. Educators, researchers, and stakeholders in the field of education will derive valuable insights into the transformative power of AI and its implications for teaching and learning.